Using artificial neural networks to estimate snow water equivalent from snow depth. Issue 3 (2nd July 2020) - Odry, J.; Boucher, M. A.; Cantet, P.; Lachance-Cloutier, S.; Turcotte, R.; St-Louis, P. Y.
Abstract: Snow water equivalent (SWE) is among the most important variables in the hydrological modelling of high latitude and mountainous areas. While manual snow surveys can directly provide SWE measurements, they are time consuming and costly, especially compared to automated snow depth measurements. Moreover, SWE is strongly correlated to snow depth. For this reason, several empirical equations relating snow depth to SWE have been proposed. The present study investigates the potential of artificial neural networks for estimating SWE from snow depth and commonly available data, and the proposed method is compared to existing, regression-based methods. An ensemble of multilayer perceptrons is constructed and trained using gridded meteorological variables and a data set of almost 40, 000 SWE and depth measurements from the province of Quebec (eastern Canada). Overall, the proposed artificial neural network-based method reached a RMSE of 28 mm and outperforms by 17% a series of empirical equations for estimating the SWE of an independent set of measurement sites. Nevertheless, all the tested methods demonstrated limits to estimate lowest values of snow bulk density.